2018
DOI: 10.1093/jas/sky338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with lysozyme during late gestation and lactation stage on the performance of sows and their offspring1

Abstract: This study investigated the effects of supplementing sow diets with lysozyme during the late gestation to lactation stage on the performance of sows and their offspring. Sixty sows (Yorkshire × Landrace, 3 to 6 of parity) at day 85 of gestation were allocated to the following 3 dietary treatments: 1) sows fed a basal diet from late gestation to lactation (control, n = 20), 2) sows fed a basal diet with lysozyme 150 g/t (LZM 150, n = 20), and 3) sows fed a basal diet with lysozyme 300 g/t (LZM 300, n = 20). Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Consistent with this hypothesis, lipocalin-2 and pro-inflammatory cytokines TNF-α in feces were decreased in the LZM 150 and 300 groups, while the IL-10 (anti-inflammatory cytokines) increased in the LZM 150 group on days 7 and 21 of lactation. Consistent with these findings, our previous study found that LZM 150 and LZM 300 increased IL-10 in serum on day 7 of sow lactation, and had a tendency to enhance IL-10 in serum on day 1 of lactation 22 , and previous studies also found that lysozyme are involved in modulating the inflammatory response 14,15 . Cytokines regulate both immune responses 52 and nutrient distribution which, characterized by proinflammatory cytokines, induce more nutrients to enter the immune response rather than being used for growth 53,54 .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Consistent with this hypothesis, lipocalin-2 and pro-inflammatory cytokines TNF-α in feces were decreased in the LZM 150 and 300 groups, while the IL-10 (anti-inflammatory cytokines) increased in the LZM 150 group on days 7 and 21 of lactation. Consistent with these findings, our previous study found that LZM 150 and LZM 300 increased IL-10 in serum on day 7 of sow lactation, and had a tendency to enhance IL-10 in serum on day 1 of lactation 22 , and previous studies also found that lysozyme are involved in modulating the inflammatory response 14,15 . Cytokines regulate both immune responses 52 and nutrient distribution which, characterized by proinflammatory cytokines, induce more nutrients to enter the immune response rather than being used for growth 53,54 .…”
Section: Discussionsupporting
confidence: 82%
“…Diets supplemented with lysozyme decreased sows' acetate, butyrate and SCFAs on day 7 of lactation, while they decreased the butyrate on day 21 of lactation compared with the control treatment. Based on our previous data, sows on lysozyme diets didn't have any difference in back fat, weight increase during the gestation period or weight loss during the lactation period when compared with sows in the control treatment 22 . It seems that the decrease of the SCFAs didn't affect sows' lipid and glucose metabolism.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations